Peran Pemerintah Desa dalam Pengembangan Usaha Mikro Kecil dan Menengah di Desa Sukajadi Kecamatan Sadananya Kabupaten Ciamis - Yuni Guntari; Dini Yuliani; Rindu Garvera (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) are business activities that are able to expand employment opportunities and provide broad economic services to the community, and can play a role in the process of equalizing and increasing community income and play a role in realizing national stability, especially economic stability. Strategy is an integrated plan designed to achieve certain goals, taking into account existing resources and the surrounding environment. This research is motivated by the lack of business capital owned by MSME owners, limited human resources, lack of market place for MSME marketing and lack of provision of facilities from the village government. The formulation of the research problem is What is the Village Government's Strategy for Organizing Micro, Small and Medium Enterprises in Sukajadi Village, Sadananya District, Ciamis Regency? The method used in this research is qualitative research methods. The data collection techniques are using interviews, observation and documentation. Data processing/analysis techniques in this research are data reduction, data presentation and data validity. This research was carried out in Sukajadi Village, Sadananya District, Ciamis Regency.